Quantity and quality of solid wastes produced in dental offices of babol city - Abdoliman Amouei; Hossein Faraji; Amid Khosravi samani; Mahmood Khosravi Samani (Babol University of Medical Sciences, 2016)
Introduction: Dental wastes due to having bacterial disease-causing agents and toxic chemicals are categorized in hazardous wastes. The aim of this study was to evaluate the quantity and composition of dental waste produced by general and specialized dental offices in babol city. Materials &Methods: From all dental offices (170 and 40 dental offices were related to general and specialized respectively) in Babol city, 20 general and 5 specialized offices were randomly selected. Waste samples were collected three times a week (Sunday, Monday and Tuesday), 50 sub-groups were separated and weighted by a digital scale with accuracy of 0.01 gram. The data were presented by excel and word software in figures and tables. Results: The total wastes of general and specialized offices were 11829 and 2831.5 kg/year, respectively. The percentages of domestic-type, infectious, pharmaceutical and toxic wastes in general dental offices were 52.5%, 42.5%, 4.7% and 0.3%; and in specialized offices were 42.5%, 50%, 7% and 0.5%, respectively. Most components in a variety of dental waste included plastic, paper, plaster molds, glass and metal. Conclusion: Due to the large contents of plastic, paper, plaster molds, glass and metals in domestic- type and infectious wastes produced in the general and specialized dental offices, it is necessary to manage the wastes and their separation and recycling in source place.